HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KETERAMPILAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK AL-MUJAHADAH KOTA PEKANBARU - Yati, Indi Suhari; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the relationship between Emotional Quotient with Fine Motor Skills of children aged 5-6 years in kindergarten Al-Mujahadah Pekanbaru. The population in this study is children aged 5-6 years in kindergarten Al-Mujahadah Pekanbaru, the study sample as many as 45 children were taken using Taro Yamane formula. The method used is the technique of Pearson Chi Square to see the relationship between the variables of Emotional Quotient and Fine Motor Skills of children aged 5-6 years in kindergarten Al-Mujahadah Pekanbaru. Data collection techniques were used that observation. Based on the results obtained by testing the hypothesis that there is a positive and significant relationship between emotional Quotient and Fine Motor Skills of children aged 5-6 years in kindergarten Al-Mujahadah Pekanbaru. It can be seen from the value of the Chi Square coefficient between Emotional Quotient with Fine Motor Skills for   count = 7.174. And  table = 5.991. Then  count>  table (7.174> 5.991) then h0 refused and ha accepted. It means there is a positive relationship between Emotional Quotient with Fine Motor Skills 5-6 years old children in kindergarten Al-Mujahadah city of Pekanbaru.